1995
DOI: 10.1002/gcc.2870140107
|View full text |Cite
|
Sign up to set email alerts
|

Balanced translocation in a neuroblastoma patient disrupts a cluster of small nuclear RNA UI and tRNA genes in chromosomal band Ip36

Abstract: Chromosomal band 1p36 probably harbours several neuroblastoma suppressor genes. A neuroblastoma patient has been described with a constitutional balanced translocation, t(1;17)(p36;q12-21). Cytogenetically, no loss of chromosomal material was visible. The 1p36 translocation breakpoint could therefore have inactivated one allele of a tumour suppressor gene, thus predisposing the patient to develop neuroblastoma. We localized this breakpoint by pulsed field gel electrophoresis, analysis of yeast artificial chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 27 publications
1
10
0
Order By: Relevance
“…A constitutional translocation t( 1; 17)(p36.31-36.13;q11.2-12) has been identified in a patient with neuroblastoma (Laureys et al, 1990;van der Drift et al, 1995). Although it is possible that this translocation signals the site of a putative suppressor, mapping studies revealed that the break on l p occurred in a complex and repetitive DNA region and disrupts a cluster of small nuclear RNA U1 and tRNA genes at AZ2MIZIPND without an obvious relationship to neuroblastoma.…”
Section: Constitutional Changesmentioning
confidence: 95%
“…A constitutional translocation t( 1; 17)(p36.31-36.13;q11.2-12) has been identified in a patient with neuroblastoma (Laureys et al, 1990;van der Drift et al, 1995). Although it is possible that this translocation signals the site of a putative suppressor, mapping studies revealed that the break on l p occurred in a complex and repetitive DNA region and disrupts a cluster of small nuclear RNA U1 and tRNA genes at AZ2MIZIPND without an obvious relationship to neuroblastoma.…”
Section: Constitutional Changesmentioning
confidence: 95%
“…Loss of chromosomal material on 1p is frequently associated with an unbalanced translocation with the long arm of chromosome 17, t(1;17). Unfortunately, this has not led to the identification of important genes in the chromosomal breakpoint areas, due to the fact that the breakpoints are highly variable on both chromosomes van der Drift et al, 1995). Efforts to define the SRO and putative tumor suppressor genes by cytogenetic and molecular analyses of large tumor cohorts and cell lines have identified at least two different SROs and one region of homozygous deletion (HD).…”
Section: Allelic Loss At 1pmentioning
confidence: 98%
“…Whereas a few translocations present in constitutional DNA have been characterized at the gene and base pair level in NB patients [9][11], only one unbalanced somatic translocation has been explored at this level in sporadic NB [12]. The full characterization of the der(1)t(1;17) in the CLB-Bar cell line revealed that it was more complex than expected due to the presence of an interstitial 4p telomeric sequence between chromosome 1p and 17q and that three different genes were disrupted by the translocation breakpoints.…”
Section: Introductionmentioning
confidence: 99%